Sosialisasi Kebijakan Pidana dalam Mencegah Terjadinya Kecelakaan Transportasi Laut Demi Keselamatan dan Keamanan Pelayaranan Nasional - Indra Yudha Koswara; Hana Faridah (LPPM UNINUS, 2022)
Transportation is a system that has facilities and infrastructure, transportation services provide guarantees not only guarantees for safety, but also include certainty and security of transportation users, both people and / or goods. The purpose of implementing the 53 Shipping Real Work Lecture (KKN) is to provide socialization about criminal regulations in an effort to prevent the prohibition of sea transportation for the safety and security of national shipping. The method of implementing KKN is carried out online by using social media as a means of finding data, discussing with partners, socialization, and counseling to the community. This is then packaged in the form of a webinar with predetermined themes, topics, and studies. Based on the results of the activity, it can be concluded that most people still do not understand the importance of shipping safety and security for the benefit of users of sea transportation services, this is due to the low understanding of regulations, less disciplined enforcement officials, and the culture of the community itself which is more concerned with achieving goals than the safety and security of shipping.